A loss‐of‐function allele of OsHMA3 associated with high cadmium accumulation in shoots and grain of Japonica rice cultivars. (16th June 2016) - Yan, Jiali; Wang, Peitong; Wang, Peng; Yang, Meng; Lian, Xingming; Tang, Zhong; Huang, Chao‐Feng; Salt, David E.; Zhao, Fang Jie
Abstract: Excessive cadmium (Cd) accumulation in rice poses a risk to food safety. OsHMA3 plays an important role in restricting Cd translocation from roots to shoots. A non‐functional allele of OsHMA3 has been reported in some Indica rice cultivars with high Cd accumulation, but it is not known if OsHMA3 allelic variation is associated with Cd accumulation in Japonica cultivars. In this study, we identified a Japonica cultivar with consistently high Cd accumulation in shoots and grain in both field and greenhouse experiments. The cultivar possesses an OsHMA3 allele with a predicted amino acid mutation at the 380 th position from Ser to Arg. The haplotype had no Cd transport activity when the gene was expressed in yeast, and the allele did not complement a known nonfunctional allele of OsHMA3 in F1 test. The allele is present only in temperate Japonica cultivars among diversity panels of 1483 rice cultivars. Different cultivars possessing this allele showed greatly increased root‐to‐shoot Cd translocation and a shift in root Cd speciation from Cd―S to Cd―O bonding determined by synchrotron X‐ray absorption spectroscopy. Our study has identified a new loss‐of‐function allele of OsHMA3 in Japonica rice cultivars leading to high Cd accumulation in shoots and grain. Abstract : Excessive cadmium (Cd) accumulation in rice poses a risk to food safety. The tonoplast transporter OsHMA3 plays an important role in restricting Cd translocation from roots to shoots. Here, we identify a new loss‐of‐function allele of OsHMA3 in Japonica rice cultivars associated with high Cd accumulation in shoots and grain.